CRISPR/Cas12a-enhanced single-molecule counting for sensitive detection of flap endonuclease 1 activity at the single-cell level. Issue 33 (4th April 2023) - Zhao, Ning-ning; Tian, Xiaorui; Ma, Fei; Zhang, Chun-yang
Abstract : We develop a new fluorescent biosensor for flap endonuclease 1 assay based on CRISPR/Cas12-enhanced single-molecule counting. Abstract : We develop a new fluorescent biosensor for flap endonuclease 1 (FEN1) assay based on CRISPR/Cas12-enhanced single-molecule counting. This biosensor is simple, selective, and sensitive with a detection limit of 2.325 × 10 −5 U and it is applicable for inhibitor screening, kinetic parameter analysis, and quantifying cellular FEN1 with single-cell sensitivity.